Social norms and economic incentives in the welfare state - Lindbeck, Assar; Weibull, Jorgen W.; Nyberg, Sten (1999)
This paper analyzes the interplay between social norms and economic incentives in the context of work decisions in the modern welfare state. We assume that to live off one's own work is a social norm, and that the larger the population share adhering to this norm, the more intensely it is felt by the individual. Individuals face two choices: one economic, whether to work or live off public transfers; and one political, how large the transfer should be. The size of the transfer and the intensity of the social norm are determined endogenously in equilibrium. - Reproduced
Keywords: Social policy